Improvement of Students’ Ability to Analyzing Cases on Case Studies Through Journal and Learning Log - Ahmad, Riska (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2017)
The purpose of this research is to improve the ability of students in guidance and counseling  to  analyzing the case through journals and learning logs This research is classroom action research consists of two cycles. The research phase consisted of planning, implementation, observation and reflection. The research subject are students in guidance and counseling while they are in sixth semester, totaling 20 people who were taking courses in Case Study. The research instrument is the observation guidelines, assessment rubrics and documentation of case studies in the form of journals and learning logs, and case study reports. The study was conducted collaboratively with student magister’s program guidance and counseling. The results showed that in cycle 1 students are able to identify cases, to develop ideas about the case, select and use instruments to analyze the cause of the problem. The results of the research cycle 2, showed 17 of the 20 students were able to analyze the cause of the problem, select the type of service and provide appropriate assistance in accordance with problem cases. Overall value obtained by the students in the subject of Case Studies also increased. In terms of the ability of explanation of the concept, the concept of truth and creativity, based on the ratings given by fellow students of average ability students were in either category, although there is less good, as are associated with the activity of the opinion and the quality of the opinions expressed.